2019
DOI: 10.1021/acs.energyfuels.9b02189
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Characteristics of Arsenic and Lead during Coal Combustion

Abstract: The study of the transformation of heavy metals during the coal combustion process is of great significance to controlling their emission. In this study, three coals with different contents of arsenic (As), lead (Pb), and mineral elements were selected. The experiments were conducted at 900−1300 °C using a drop tube furnace system. The transformation of As and Pb during the combustion processes of the three coals was obtained. It was found that both the gaseous and particulate phases were important forms of As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…This could be induced by the emission transfers from the city of Selenginsk located 45 km from the coast (Figure 1), as well as by the superposition of the distribution fields of impurities from the pollution sources of the Irkutsk region. The maximum accumulation of lead (Figure 3 c) was detected in the Baikal Natural Biosphere Reserve in 2019-2020 (points 17,18). This could be caused by the reserve location in the direction of the main air mass transfers from the industrial centers of the Irkutsk region (Figure 1) and the large amount of precipitation that fell on its territory (Table 4).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This could be induced by the emission transfers from the city of Selenginsk located 45 km from the coast (Figure 1), as well as by the superposition of the distribution fields of impurities from the pollution sources of the Irkutsk region. The maximum accumulation of lead (Figure 3 c) was detected in the Baikal Natural Biosphere Reserve in 2019-2020 (points 17,18). This could be caused by the reserve location in the direction of the main air mass transfers from the industrial centers of the Irkutsk region (Figure 1) and the large amount of precipitation that fell on its territory (Table 4).…”
Section: Resultsmentioning
confidence: 95%
“…In the second factor for ions and microcomponents, soil elements -aluminum, calcium and iron -were mixed with coal combustion sources -chromium, arsenic and lead. Soil sources included soil particles from long-range transport, road dust, roadbed treatment chemicals, and local soils [14][15][16][17][18][19] .…”
Section: Resultsmentioning
confidence: 99%
“…The Pb contents in the products were measured. The methods were introduced in our previous study . The results are listed in Table .…”
Section: Experimental and Calculational Settingsmentioning
confidence: 99%
“…In a coal-fired system, the migration of Pb to the solid phase occurs in two stages: during the high-temperature combustion stage, it is retained due to its own thermal stability or interaction with other components in the coal; during the flue gas cooling stage after combustion, it migrates to fly ash particles due to chemical adsorption, physical adsorption, and condensation. , Previous studies have shown that coal blending and mineral addition can enhance Pb retention by minerals during high-temperature coal combustion, thereby reducing Pb emissions. Studying the retention mechanisms of the mineral components on Pb in high-temperature environments is beneficial for the development of regulatory technologies.…”
Section: Introductionmentioning
confidence: 99%
“…As a volatile hazardous trace element, arsenic has attracted much attention due to its extreme toxicity to human health . Coal combustion is widely regarded as the main source of anthropogenic arsenic emission, which receives great environmental attention. , Due to the domestic enormous coal consumption, the government has taken positive and stringent measures to control arsenic discharged from coal combustion in recent years, and the total amounts of atmospheric arsenic emission by coal-fired power plants were expected to reduce to 215.57 tons in 2020. , Arsenic mainly evaporates in the form of As 2 O 3 (g) during coal combustion and tends to condense on fine-grained particles with a decrease in the flue gas temperature, , which is difficultly captured by cyclone separators, dust collectors, and other air pollution control devices. Accordingly, it is essential to further develop arsenic removal technology, which aims to convert As 3+ vapor into less toxic As 5+ arsenate at high temperature and enrich in coarse particles as much as possible for subsequent removal by dedusting devices.…”
Section: Introductionmentioning
confidence: 99%